2021
DOI: 10.1017/wsc.2021.45
|View full text |Cite
|
Sign up to set email alerts
|

Weedy rice update in Arkansas, USA, and adjacent locales

Abstract: Weedy rice (Oryza sativa L.) is among the most problematic weeds in rice (Oryza sativa L.) production. The commercialization of herbicide-resistant (HR) rice nearly two decades ago provided an effective tool to manage weedy rice; however, resistance evolution and volunteer HR hybrid rice kept weedy rice at the forefront of rice weed control needs. This research aimed to assess the prevalence and severity of weedy rice infestations, identify production practices that may have contributed to an increase in weedy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Hybridization of sensitive weedy rice and IMI-resistant rice carrying the Ser653Asn substitution leads to resistance in weedy rice. Some methods have been proposed to mitigate IMI-resistant weedy rice populations, such as the introduction of Provisia ® rice resistant to aryloxyphenoxypropanoates (APP, e.g., quizalofop) and biotechnological-based strategies (Roma- Burgos et al, 2021). IMI-resistant weedy rice can be controlled using quizalofop-resistant rice technology within a short period (Burgos et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization of sensitive weedy rice and IMI-resistant rice carrying the Ser653Asn substitution leads to resistance in weedy rice. Some methods have been proposed to mitigate IMI-resistant weedy rice populations, such as the introduction of Provisia ® rice resistant to aryloxyphenoxypropanoates (APP, e.g., quizalofop) and biotechnological-based strategies (Roma- Burgos et al, 2021). IMI-resistant weedy rice can be controlled using quizalofop-resistant rice technology within a short period (Burgos et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Provisia rice constituted 2.7% of the total rice hectares planted in Arkansas in the growing season of 2020. However, when evaluated in commercial rice trials (Frizzell et al 2021, Hardke 2021, quizalofop-resistant rice has had lower yield potential resulting in reduced commercial adoption even though quizalofop is another tool for managing herbicide-resistant weedy rice (Roma-Burgos et al 2021). A single-point mutation confers the resistance mechanism in quizalofop-resistant rice, and the presence of the resistant ACCase allele can be detected at low cost with standard molecular biology laboratory equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sublethal glyphosate rates are detrimental to rice and have been shown to cause substantial injury and yield reductions ranging from 18% to 89% when plants were exposed to a 140 g ae ha −1 (1/8× rate of labeled use rate of 1,120 g ae ha −1 ) at the 3-to 4-leaf to the booting rice stages (Kurtz and Street 2003). In Arkansas, a survey conducted in 2020 showed that glyphosate was used as a preplant option individually or in combination with protoporphyrinogen oxidase inhibitors, synthetic auxins, and diterpene biosynthesis inhibiting herbicides on 60% of total rice fields surveyed (Roma-Burgos et al 2021). Therefore, glyphosate applied preplant could potentially cause injury to nearby emerged conventional and quizalofopresistant rice fields in early rice growth stages.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, quizalofop‐resistant rice was grown on 39,450 and 30,740 acres, accounting for 2.7 and 6.5% of the total acreage under rice production in Arkansas and Louisiana, respectively, and is expected to increase rapidly in future growing seasons (Hardke, 2021; Harrell, 2021). Quizalofop‐resistant rice technology is needed because of the continuous evolution of herbicide‐resistant grass weeds (Roma‐Burgos et al., 2021) including problematic weeds such as barnyardgrass [ Echinochlo a crus‐galli (L.) P. Beauv.…”
Section: Introductionmentioning
confidence: 99%